Jejak Sejarah Kesultanan Pontianak (Kajian Inskripsi Situs Makam Batu Layang) - Alfan Firmanto (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
Kadriyah Pontianak Sultanate is the youngest Islamic kingdom in Indonesi. It is established on 23th October, 1771 AD or 12th Rajab 1185 H. Many things that have not been revealed in the history of Pontianak Sultanate founded by Abdurrahman Al-Sharif Qadrie. This research tries to uncover the history of the sultanate of Pontianak through inscriptions on the tomb of the Sultan in Batu Layang grave sites in Pontianak. From hundreds of tombs in the site there are eight main tombs of the kings who ruled Pontianak Sultanate. From the inscription that is found on the tomb of the Sultan, this study migth uncover a bit of historical periodization of Pontianak Sultanate